Konseling Pastoral Bagi Jemaat Yang Mempunyai Luka Inner Child - Stefanus Christianto Yuwono (PT. Giat Konseling Nusantara, 2024)
Inner Child is part of our past trauma and usually affects a person's life in the future including his personality. Therefore, when an Inner Child is injured, it will influence us as an adult in making decisions and dealing with other people. Inner Child is a concept that describes the childish nature and attitude that everyone has. Even so, the conditions that exist in each individual are not the same because they are formed from experiences when they were children. The Inner Child can be described as the part of us that doesn't grow up and remains a child. That is, this part continues to stay and hide inside a person. This section holds tightly to every memory and emotion we have experienced as a child, both good and bad. Unfortunately, this then also absorbs any negative energy, be it behavior or speech from the person we think should provide a sense of security. The Inner Child is one of the components that make up our character. Therefore, we need to know, accept, and connect with the inner child within ourself.